Risk-shifting, equity risk, and the distress puzzle - Li, Keming; Lockwood, Jimmy; Miao, Hong (Journal of Corporate Finance, 2017)
Higher default probabilities are associated with lower future stock returns. The anomaly cannot be explained by strategic shareholder actions, traditional risk factors, characteristics, or mispricing, but, instead, is consistent with a risk-shifting hypothesis. Consistent with the risk-shifting hypothesis, we find that distressed firms tend to overinvest, destroy value, and exhaust their cash flows. Effects are concentrated in firms with wide credit spreads, firms with no convertible debt, and in cases where CEOs receive above-average equity-based compensation. As default risk rises, credit spreads rise, equity betas fall, and equity returns fall.